2022
DOI: 10.3390/biomedicines10081817
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: Guardian of Skin Barrier

Abstract: Autophagy is a major degradation pathway that removes harmful intracellular substances to maintain homeostasis. Various stressors, such as starvation and oxidative stress, upregulate autophagy, and the dysregulation of autophagy is associated with various human diseases, including cancer and skin diseases. The skin is the first defense barrier against external environmental hazards such as invading pathogens, ultraviolet rays, chemical toxins, and heat. Although the skin is exposed to various stressors that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 120 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…Autophagy enhances normal cell survival by lysosomally degrading damaged cells and their contents, thereby maintaining environmental homeostasis and energy levels ( 68 ). The autophagic process can be divided into three main steps: activation of autophagy, autophagosome formation, and fusion degradation ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy enhances normal cell survival by lysosomally degrading damaged cells and their contents, thereby maintaining environmental homeostasis and energy levels ( 68 ). The autophagic process can be divided into three main steps: activation of autophagy, autophagosome formation, and fusion degradation ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibiting autophagy by depleting Beclin-1 can effectively hinder the proliferation and differentiation of keratinocytes [ 32 ]. Based on these findings, Kim et al [ 33 ] proposed autophagy as a pivotal guardian of the skin barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, perilesional skin in patients showed increased autophagy in comparison to surrounding active lesions, as assessed by increased expression of autophagy-related proteins (autophagy-related gene5 (Atg5) and light chain 3 (LC3)), concurrently with the down-modulation of sequestosome 1 (SQSTM1/p62) [ 62 ]. These phenomena raise the hypothesis of a protective role for autophagy in vitiligo [ 63 ]. Further studies have showed that autophagy inhibition exacerbates adverse metabolic effects in non-lesional vitiligo cells [ 64 ], suggesting that autophagy may be an adaptive response to continuous metabolic alterations for a protective attempt to antagonize degenerative processes and to enhance survival in normal vitiligo skin.…”
Section: Antioxidative Defense and Cellular Responses To Ros Accumula...mentioning
confidence: 99%